Analisis Pengaruh Perputaran Piutang (Receivable Turn Over) dan Pengaruh Perputaran Persediaan (Inventory Turn Over) Terhadap Laba Sebelum Bunga dan Pajak (Earning Before Interest and Tax) Pada PT. Solusi Bangun Indonesia Tbk Periode 2019 – 2021 - Asrul; Erma Fajriyah (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2022)
Earning Before Interest and Tax (EBIT) is a fundamental analysis that is used by internal (management) and external (Investors) to help identify the company's ability to generate profits. The results of EBIT allow management to be able to know, pay debts, and finance ongoing operations. Meanwhile, for investors, it is a consideration to buy shares in a company and identify the company's operating profit. EBIT can also be helpful when investors compare two companies that are in the same industry.Purpose the paper is to analyze the effect of Receivable Turn Over (receivable turnover) and the effect of Inventory Turn Over (inventory turnover) on EBIT, the sample used in this study is the financial statements of PT Solusi Bangun Indonesia Tbk for the period 2019 – 2021 (3 years). Meanwhile, the analytical tool used in this research is quantitative analysis, namely the activity ratio method and the profitability ratio method.